KARAKTERISASI HASIL PENGELASAN GTAW PADA BAJA KARBON RENDAH DENGAN VARIASI SUDUT GEOMETRI ELEKTRODE DAN BESAR ARUS PENGELASAN - Lisa Agustriyana (INFO-TEKNIK, 2018)
In the application of welding "GTAW" has several advantages such as welding results do not need to be cleaned from slag or corrosion residue. Due to the above-mentioned advantages, the precise determination of weld parameters and offset by the welding skills of welded characteristics will be affected. The purpose of this research is to know the characteristic of GTAW welding on low carbon steel, by observing the shape of weld bead and supported by the result of macro photo of welding result from various variations of currents and variations of the angle geometry of tungsten electrode. The method used in this study is an experimental method, with treatment of parameters of parameters of current and parameters of angle geometry variation of tapering of tunsten electrode. Analyze method is done to welding result and macro photo of T connection weld result. From the analysis of GTAW weld metal form with type T connection through variation of electrode geometry angle and strong welding current in this research, can be drawn some conclusions, among others, from some variation of weld geometry angle which gives good shape of welding characteristic and deep penetration is angle 300 of ampere 90 A.